Innovation, Entrepreneurship and Governance for Sustainable Development of Africa’s Agri-food System - Gurib-Fakim, Ameenah (Technical Centre for Agricultural and Rural Cooperation, 2015)
Africa has the human capital to transform its agricultural sector Growth in urban markets provides new opportunities for enterprise development Investments in science, technology, engineering and math must be increased Bold leadership, as well as policies that promote R&D collaboration and provide incentives for partnering with the private sector, should be implemented.